آثار ظاهرة غسيل الأموال على الاقتصاد العراقي وسبل معالجتها (دراسة تطبيقية ) (المجلة العراقية للعلوم الاقتصادية, 2018)
The phenomenon of money laundering is an economic crime that has negative effects on economic, social and political activities in a country such as Iraq. Iraq is a new country in the issuance of anti-money laundering laws. After the spread of this phenomenon, the first law was issued in this regard,is Law No. 93 of 2004, then Law No. 39 of 2015 was issued to combat money laundering and terrorism financing. The aim of the research is to confirm the validity of this hypothesis by a practical study to some private banks and using a statistical program. To study of the most important banking procedures to combat this phenomenon and reduce it in order to achiere the Economic and social and political,stability The study has been put several recommendations and precautionary measures for banks in order to reduce this phenomenon and reduce the negative impact.Key words to research : (Money laundering – Banks- Statistical Program –Questionnaire form ).